The lactase persistence ‐13910C>T polymorphism shows indication of association with abdominal obesity among Portuguese children. (9th January 2013) - Albuquerque, David; Nóbrega, Clévio; Manco, Licínio
Abstract Aim The ‐13910C>T single nucleotide polymorphism located upstream of the lactase gene (LCT) was found tightly associated with lactase persistence in European populations. Recently, it was also associated with body mass index (BMI) and obesity in European adults. The aim of this study was to test the association of ‐13910C>T polymorphism with obesity‐related traits and risk of obesity in children. Methods We genotyped 580 Portuguese children (6–12‐year‐olds) for the ‐13910C>T polymorphism using TaqMan probes by real‐time PCR. Anthropometric measurements were assessed in all children. Obesity was defined according to the International Obesity Task Force (IOTF) cut‐offs and abdominal obesity using the sex and age‐specific ≥90th waist circumference percentile. Results We found indication for an association between the‐13910*T allele and children abdominal obesity (odds ratio [OR] = 1.41; 95% confidence intervals [CI]: 1.03–1.94; p = 0.030). Under the dominant model, the indicative association was observed between the LCT‐13910 CT/TT genotypes and abdominal obesity, remaining significant after adjustment for age and gender (OR = 1.65; 95% CI: 1.04–2.60; p = 0.029). No association was detected with the risk of obesity (p = 0.350). Conclusion Our results suggest that the ‐13910C>T polymorphism may predispose to abdominal obesity in Portuguese children. The association with BMI or risk of obesity, previously observed in adults, was not confirmed.